Review: Therapeutic advances in functional gastrointestinal disease: irritable bowel syndrome - Alexandru Gaman; Maria Cristina Bucur; Braden Kuo (Therapeutic Advances in Gastroenterology, 2009)
Reported prevalence rates of irritable bowel syndrome (IBS) are between 8% to 20% in the US general population with an average medical expenditure of US$1.35 billion direct and US$205 million indirect costs. Current pathophysiologic theories are based on abnormalities of both the brain and gut, thus setting a new stage for current and future therapeutic approaches. There are numerous treatment options in IBS acting centrally and peripherally by influencing motility and visceral sensitivity. Clinical evidence is variable; however, newer emerging treatments are being evaluated using better-designed clinical trials. Accurate assessment of IBS drug efficacy is still hampered by heterogeneity of the IBS population. Novel methods such as pharmacogenomics or brain imaging may be helpful in the future to better understand and characterize IBS patient subtypes, and this in turn will lead to more specific and efficient therapeutic options. Patient subpopulation measurement of side effects is also a clinical challenge and further understanding could improve treatment efficacy by enhancing the patient compliance.